The Application of Agency Theory in Supply Chain Finance: A Case of Indonesian Manufacturing Firms - Hadiati Fitri; Elmanizar .; Andhyka Tyaz Nugraha; Andi Yakub; Bambang Priyo Cahyono (International Journal of Supply Chain Management, 2019)
The prime objective of the current study is to explore the relationship between supply chain operational performance and firm supply chain management in the reference of agency theory. To further explain the role of agency theory, in the supply chain management we have examined the direct and indirect impact of supply chain operational performance on firm supply chain management. The SMART-PLS is used to achieve the objective of the current stud. The data is collected from the operation managers, production managers and finance managers of manufacturing firms listed in Indonesian Stock Exchange. The results of the study have shown a great deal of agreement with our proposed hypothesis. The corporate governance index comprising of board characteristics appears as a moderator in the relationship between supply chain operational performance and firm supply chain management. The results of the current study are also providing support to agency theory and resource base theory. The study which is among pioneering studies on the issue will be helpful for policy makers and managers in understanding the role of agency theory in supply chain management.